Evaluasi Efektivitas Manajemen Risiko dalam Menghadapi Tantangan Bisnis dan Kerugian Usaha pada UMKM: Studi Kasus Mie Ayam Baso Matahari - Gibran Siregar, Muhammad; Ramdani, Dimas Muhammad; Maharani, Pina Aulia; Suwarna, Asep (Universitas Serambi Mekkah, 2024)
MSMEs (Micro, Small and Medium Enterprises) play an important role in the Indonesian economy, especially in the culinary sector. One UMKM that has successfully survived and thrived amidst business challenges is Mie Ayam Baso Matahari, established in 2019. This research aims to evaluate the effectiveness of risk management in facing business challenges and financial losses experienced by Mie Ayam Baso Matahari, particularly during the COVID-19 pandemic. The research employs qualitative methods, utilizing in-depth interviews, observations, and document analysis for data collection. The findings reveal that Mie Ayam Baso Matahari implements a comprehensive risk management strategy, including risk identification in the areas of operations, finance, human resources, and marketing. Adaptations made, such as product diversification and the use of digital platforms for marketing, have contributed to the recovery of the business.